(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This study investigates the linguistic and extralinguistic components of translating sociopolitical materials. The study focuses on the obstacles that translators encounter while transmitting political beliefs, social issues, and cultural subtleties across many languages. By examining diverse translation tactics and approaches, this research hopes to offer insight on how translators traverse the complex interaction of language, culture, and politics in order to effectively express the intended content of sociopolitical writings. Finally, this study aims to contribute to a better understanding of the function of translation in molding public discourse and promoting cross-cultural communication in a globalized society.